EVALUASI RELOKASI PEDAGANG KAKI LIMA TERHADAP KESEJAHTERAANNYA - anti, Tri Yuli; Panjawa, Jihad Lukis (Jurnal Ekonomi Pembangunan (JEP) UHO, 2020)
This study identifies the influence of a relocation of street vendors (PKL) the square and the level of income received at Purbalingga Food Center (PFC). The purpose of this study is to determine how much influence the relocation of Purbalingga street vendors or the effect that occurs after the relocation has an impact on the level of income received and also the level of welfare of traders at the Purbalingga Food Center. The research shows the level of welfare can be measured from the income received. Can find out how the response of the street vendors who sell in the PFC area. One of the realization of the relocation of street vendors is that one of them is supported by the Department of Industry and Trade which regulates street vendors directly and also the ministry of trade. The data used in this study are primary data by observing street vendors at the Purbalingga Food Center (PFC). The method used in this research is the analysis method. The analytical tool used is paired-samples t test.Â